Medical and sanitary substantiation of the safety of pesticide use with 3RIVE 3D technology - Kondratiuk, Mykola; Borysenko , Andriy; Antonenko , Anna; Aleksiichuk , Vasyl; Melnychuk , Fedir (The Ukrainian Scientific Medical Youth Journal, 2024)
оne factor of significant importance for reducing the pesticide load on target objects and the biocenosis as a whole is the method of introducing Plant Protection Products (PPPs). In accordance with the EU Directive, procedures for the use of machinery and technologies for the safe application of pesticides have been regulated and implemented. The behavior of the active substance - bifenthrin - was investigated through a field experiment; soil and plant samplings were carried out in accordance with established methodological recommendations. 3RIVE 3D is an innovative method of insecticide application. The active substance bifenthrin does not practically migrate across the profile in sandy and organic-rich soils. The compound is relatively insoluble in water, which prevents its concentration in aquifers. When applying the Brigade 3Rive 3D product, the half-life (τ50) of bifenthrin was 3.6 days, τ95 – 15.4 days, and τ99 – 26.7 days, with a degradation rate constant of 0.19 days-1, which is lower than the average values obtained in other countries of the European region. The potential leaching index was also calculated, taking into account the half-life established in the agroclimatic conditions of Ukraine, which was -0.76 a.u., indicating an extremely low probability of leaching into groundwater. Based on the organic carbon sorption constant, which is 236610 mL/g – class 5 (non-mobile compound), the integral hazard vector for bifenthrin is 51.9 points, indicating a medium hazard risk. It was found that with the application of the Brigade 3Rive 3D product using 3Rive3D technology, the half-life of bifenthrin was 3.6 days, which is lower than the average values obtained in other European region countries. According to DSanPiN 8.8.1.002-98, based on soil stability indicators, the compound can be classified as a class 4 hazard (low-hazard compounds), and in water - as a class 1 hazard (extremely hazardous).